A Wax Effigy Pierced by Three Bones: The Pharaonic Origins of a Late-Antique Cursing Ritual?. Issue 1 (1st January 2017) - Faraone, Christopher A.
Abstract : Papyrus fragments from a late-antique Greek magical handbook preserve a unique recipe that directs us to make a wax "voodoo doll" and pierce it with three bones – "the left one, the right one and the one from the back" – "of an eisphatēs ", a previously unknown Greek word that has been emended to mean "sacrificial victim" ( sphaktēs ) or "dove" ( phattēs ). Emendation is not warranted, however, because the word is probably a local and previously unknown Egyptian term for the Nile catfish, which has three distinctive nail-like spines – the right and left pectoral and the dorsal – that match those of the eisphatēs . The bone of this fish is, moreover, used in a native Egyptian cursing ritual of Pharaonic date also involving a wax "voodoo doll", that is inscribed with the bone, rather than pierced by it.